Do the companionship and community networks of older LGBT adults compensate for weaker kinship networks?. (14th March 2016) - Green, Marcus
Abstract : Purpose: – The purpose of this paper is to compare the supportive capacity of social networks of older lesbian, gay, bisexual and transsexual (LGBT) and heterosexual adults using data from Understanding Society. The principal research objective is to discern whether the companionship and community networks of older LGBT adults compensate for weaker kinship networks. Design/methodology/approach: – Understanding Society has data on the frequency of interaction with and proximity to family, friends and the wider community to quantify supportive capacity. Bivariate analyses reveal similarities and differences in network supportive capacity between older LGBT and heterosexual adults. Findings: – The study finds that older LGBT adults have significantly weaker kinship networks than do older heterosexual adults. Further to this, the companionship and community networks of older LGBT adults do not compensate for weaker kinship networks. Social implications: – In essence, this means that many older LGBT adults have weak social networks which increases the likelihood of receiving little or no social contact and informal support which may have implications for their physical and mental well-being. This could be especially problematic for individuals who have care needs where in the context of England, the provision of state funded social care is patchy. Originality/value: – This study contributes evidence to an under researched area of social network analysis. Little research has explored the social networks of older LGBT adults compared with older heterosexual adults; specifically the supportive network capacity of different types of network.